PENGARUH KARAKTERISTIK TUJUAN ANGGARAN DAN PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH STUDI PADA SKPD PEMERINTAH KOTA JAYAPURA - Agustinus Salle; Cornelia D. Matani (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
This study aims to analyze the Effect of Characteristics of Budget Objectives and Regional Financial Management on the Performance of Local Governments in Jayapura City in order to realize good governance, and to know the factors that influence the Performance of Local Government. The data collection technique used in this study was primarily by using a questionnaire through the surveymethod for Civil Servants (PNS), namely the head of the section and sub-section in the 28 Regional Government Work Unit (SKPD) of the Jayapura City Government. The sampling technique uses purposive sampling. Data analysis in this study used multiple linear regression analysis. The results of this study indicate that the characteristics ofthe Budget Objective: there is no influence between budgetary participation on the performance of local governments, there is a positive and significant influence between the clarity of budget objectives on local government performance, there is no influence between budget feedback on local government performance, there is no influence between evaluation of the budget for the performance of local governments, there is no influence between the difficulty of budget objectives on the performance of local governments, there is a positive and significant influence on regional financial management on the performance of local governments